Download presentation
Presentation is loading. Please wait.
Published byLynette Hoover Modified over 9 years ago
2
Solving 1-Step Equations
3
2 An Equation is Like a Balance
4
22
5
22
6
1-Step Equations A 1-Step Equation is an equation with 1 variable and 1 math operation. Example: x + 6 = 8 -----> Addition Equation n - 4 = 11 -----> Subtraction Equation 9k = -18 -----> Multiplication Equation y 7 = 5 -----> Division Equation
7
Inverse Operations 4 The inverse operation for addition is __________. Subtraction 4 The inverse operation for subtraction is__________. Addition 4 The inverse operation for multiplication is ________. Division 4 The inverse operation for division is _____________. Multiplication
8
In General Remember this… Addition + Subtraction - Multiplication x Division
9
Let’s Do Some Addition Equations x + 5 = 7 Since this is an addition equation, you must subtract 5 from each side to balance the equation. - 5 x = 2 x + 3 = -7 Since this is an addition equation, you must subtract 3 from each side to balance the equation. - 3 x = -10
10
Let’s Do Some Subtraction Equations x - 5 = 7 Since this is an addition equation, you must add 5 to each side to balance the equation. + 5 x = 12 x - (-3) = 8 Remember a double negative is a positive. Change -(-3) to + 3. x + 3 = 8 Now, solve the resulting addition equation. - 3 x = 5
11
Let’s Do Some Multiplication Equations 5x = 35 Since this is a multiplication equation, you must divide each side by 5 to balance the equation. 5 5 x = 7 -8x = 24 Since this is a multiplication equation, you must divide each side by -8 to balance the equation. -8 x = -3
12
Let’s Do Some Division Equations x 4 = 10 Since this is a division equation, you must multiply each side by 4 to solve the equation. (4) x = 40 r 9 = -2 Since this is a division equation, you must multiply each side by 9 to solve the equation. (9) r = -18
13
A Special Case: Whenever you have a fractional coefficient, you multiply both sides by the reciprocal. 6 m = 18
14
x + 17 = 3 - 17 x = -14 m - 8 = -9 + 8 m = -1 6k = 66 6 6 k = 11 p -5 = 2 (-5) p = -10
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.